2019
DOI: 10.1186/s12879-019-4381-9
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus prevalence and patterns of subgroup persistence identified through surveillance of pediatric pneumonia hospital admissions in coastal Kenya, 2007–2016

Abstract: Background Human metapneumovirus (HMPV) is an important respiratory pathogen that causes seasonal epidemics of acute respiratory illness and contributes significantly to childhood pneumonia. Current knowledge and understanding on its patterns of spread, prevalence and persistence in communities in low resource settings is limited. Methods We present findings of a molecular-epidemiological analysis of nasal samples from children < 5 years of age admitted with syndromic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Some proteins from HMPV, including G, M2-2, and SH, are also able to inhibit the interferon response (95), but potentially to a lesser extent than RSV, which could decrease spread in comparison. Alternatively, HMPV has been shown to establish persistent infections (96)(97)(98)(99)(100)(101). Thus, it is possible that the low replication rates of HMPV in HAE tissues may drive the virus toward persistence rather than an acute infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some proteins from HMPV, including G, M2-2, and SH, are also able to inhibit the interferon response (95), but potentially to a lesser extent than RSV, which could decrease spread in comparison. Alternatively, HMPV has been shown to establish persistent infections (96)(97)(98)(99)(100)(101). Thus, it is possible that the low replication rates of HMPV in HAE tissues may drive the virus toward persistence rather than an acute infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that co-circulation of several HMPV genotypes during a given season is a common occurrence [ 25 , 35 ]. An investigation carried out in Kenya concluded that a genotype predominating in one country in a given year was not necessarily the predominant genotype in other countries [ 6 ]. This indicates that a HMPV genotype could become the most prevalent in a specific area, but not necessarily represent the predominant circulating genotype in a broader region.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Italy identified only one A1 genotype virus among 49 children with HMPV infection, while Kong et al identified one case among 145 HMPV infections that were genotyped in China [ 37 , 38 ]. Many recent studies have failed to detect HMPV A1 cases indicating that this genotype might have become extinct [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The 180-nucleotide duplication in the G gene of HMPV was reported to be present in respiratory samples obtained in 2014 and onward in Japan and Spain [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from the clinic were collected twice weekly with a maximum of 15 samples per week (details on the sample size and sampling procedures are detailed in the referenced manuscript) 22 . Children under 60 months of age admitted to the Kilifi County Hospital with syndromic severe or very severe pneumonia were enrolled as part of a continuous respiratory virus surveillance study, with NPS samples collected (details published elsewhere 28 ). Only children considered to be appropriately aged for their school grade are included in this analysis.…”
Section: Methodsmentioning
confidence: 99%